Right ventricular functional assessment by 2D multi‐plane echocardiography prior to left ventricular assist device implantation. - Bowen, Daniel J.; Yalcin, Yunus C.; Strachinaru, Mihai; McGhie, Jackie S.; van den Bosch, Annemien E.; Soliman, Osama I.; Caliskan, Kadir (Echocardiography, 2022)
Objectives: Right ventricular (RV) failure post left ventricular assist device (LVAD) implantation is associated with increased morbidity and mortality. A novel RV multi‐plane imaging method using two‐dimensional echocardiography and electronic plane rotation (MPE) was used to quantify RV function prior to LVAD implantation and to identify potential added value in this patient population. Methods: In twenty‐five end‐stage heart failure patients (age 58.9 ± 6.8 years, 76% male), systolic function of four different RV walls (lateral, anterior, inferior and inferior coronal) were evaluated from one focussed apical view using MPE. Results: Feasibility of tricuspid annular plane systolic excursion (TAPSE) and tricuspid annular peak systolic velocity (RV‐S') measurements were high (84–100%), with lower TAPSE values measured in the inferior (14.2 ± 4.6 mm) and inferior coronal (12.3 ± 5.0 mm) walls compared to the lateral (16.3 ± 4.5 mm) and anterior walls (16.0 ± 4.5 mm). RV wall longitudinal strain (RV‐LS) measurement was most feasible in the lateral wall (80%; mean: –12.1 ± 4.2%). TAPSE and RV‐LS values were significantly reduced in patients compared to matched healthy individuals (p = <0.001). Seven (28%) patients who developed moderate to severe RV failure (RVF) early post‐implant (≤30 days) had lower pre‐implant values across all multi‐plane parameters compared to those without significant post‐implant RVF, notably four‐wall averaged TAPSE (11.1 ± 3.4 mm vs 15.9 ± 4.0 mm; p = 0.02). Conclusion: 2D MPE was highly feasible for RV wall quantification pre‐LVAD surgery, detecting differences in regional wall function. This novel method comprehensively quantifies RV wall function and could complement current pre‐LVAD screening protocols.